Experimental Analysis of the Scalability of Ethereum Blockchain in a Private Network - Ochôa, Iago S; Piemontez, Rafael; Martins, Lucas; Leithardt, Valderi Reis Quietinho; Zeferino, Cesar Albenes (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain), 2019)
Blockchain technology has aroused the interest of researchers as it ensures security and privacy in decentralized applications. One of the platforms currently used for the development of new blockchain-based solutions is the Ethereum network. This article presents an experimental analysis of the scalability of this network to identify its gas cost and performance for several contracts in a simulated private Ethereum network. The results obtained demonstrate that storage operations for large amounts of data can prevent the use of blockchain due to the high cost of gas charged for this type of operation. The experiments also pointed out that processing operations which do not store information have a small cost of gas.